2022
DOI: 10.3389/fphys.2022.1060640
|View full text |Cite
|
Sign up to set email alerts
|

Effects of flywheel resistance training on the running economy of young male well-trained distance runners

Abstract: The study aimed to investigate the effect of flywheel accentuated eccentric loading (AEL) training on the running economy (RE) of young male well-trained distance runners. Twenty-two runners participated and were randomly assigned to the flywheel (FG, n = 12) and the control group (CG, n = 10). Traditional endurance training was performed in both groups three times a week for 6-week, while traditional resistance and flywheel AEL training was added to the CG and FG respectively. Subjects performed the increment… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1

Citation Types

0
2
0

Year Published

2023
2023
2024
2024

Publication Types

Select...
3
1

Relationship

1
3

Authors

Journals

citations
Cited by 4 publications
(2 citation statements)
references
References 51 publications
0
2
0
Order By: Relevance
“…Recently, flywheel training (FT) has emerged as an efficacious strategy for a wide range of athletes to enhance sports performance (Buonsenso et al, 2023). For instance, the physical capacities of soccer players (i.e., strength, power, jump, and direction changes) (Allen et al, 2021), running economy of distance runners (Weng et al, 2022), lower-body strength and power qualities in male academy rugby players (Murton et al, 2021), and the CMJ performance of basketball players (Stojanović et al, 2021) were shown to be significantly improved using FT. Strength and conditioning practitioners may acutely or chronically improve athletes' performances with the FT as the eccentric phase is associated with a high mechanical overload .…”
Section: Discussionmentioning
confidence: 99%
“…Recently, flywheel training (FT) has emerged as an efficacious strategy for a wide range of athletes to enhance sports performance (Buonsenso et al, 2023). For instance, the physical capacities of soccer players (i.e., strength, power, jump, and direction changes) (Allen et al, 2021), running economy of distance runners (Weng et al, 2022), lower-body strength and power qualities in male academy rugby players (Murton et al, 2021), and the CMJ performance of basketball players (Stojanović et al, 2021) were shown to be significantly improved using FT. Strength and conditioning practitioners may acutely or chronically improve athletes' performances with the FT as the eccentric phase is associated with a high mechanical overload .…”
Section: Discussionmentioning
confidence: 99%
“…Recently, flywheel training (FT) has emerged as an efficacious strategy for a wide range of athletes to enhance sports performance ( Buonsenso et al, 2023 ). For instance, the physical capacities of soccer players (i.e., strength, power, jump, and direction changes) ( Allen et al, 2021 ), running economy of distance runners ( Weng et al, 2022 ), lower-body strength and power qualities in male academy rugby players ( Murton et al, 2021 ), and the CMJ performance of basketball players ( Stojanović et al, 2021 ) were shown to be significantly improved using FT. Strength and conditioning practitioners may acutely or chronically improve athletes’ performances with the FT as the eccentric phase is associated with a high mechanical overload ( Gonzalo-Skok et al, 2017 ).…”
Section: Introductionmentioning
confidence: 99%